Analysis and Optimization for Humane trap Design - Yi, Young-Joon (My University, 1974)
The stirrup type spring that is used in the Conibear series of trans was analyzed and new springs for this type of trap were designed utilizing the non-linear optimization technique.
The Jacob trap concert combined with the concept of a swinging interior mechanism for animal control was developed and optimized and four prototypes were manufactured and evaluated.
Analytical methods for predicting the theoretical energy of closing Conibear and Jacob trans at various jaw openings were developed.
Keywords: Mechanical Engineering; Mechanical Engineering